2004
DOI: 10.1002/anie.200460747
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Elucidation of a Peroxo Ni2(μ‐O2) Intermediate Derived from a Nickel(I) Complex and Dioxygen

Abstract: The preparative chemistry and reactivity of NiÀO x intermediates has advanced significantly in the past few years with the identification of a number of new structure types. The most common synthetic approach, reaction of a nickel(ii) precursor with H 2 O 2 , has yielded bis-m-oxo [1][2][3][4] and bis-msuperoxo complexes.[4] An attractive alternate route utilizes the reaction of nickel(i) complexes with O 2 . This strategy relies on, and is limited by, the ability to prepare suitable nickel(i) species. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…Riordan was the first report such a species but this Ni II –OH complex has a square planar primary coordination sphere coordination with a τ 5 value of 0.0 [22]. Levy’s nickel-hydroxido complex has a τ 5 value of 0.86, and is thus the only other Ni II –OH complex with tbp geometry [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Riordan was the first report such a species but this Ni II –OH complex has a square planar primary coordination sphere coordination with a τ 5 value of 0.0 [22]. Levy’s nickel-hydroxido complex has a τ 5 value of 0.86, and is thus the only other Ni II –OH complex with tbp geometry [23].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there are only two examples of crystallographically characterized monometallic 5-coordinate Ni II –OH complexes. Riordan has prepared a square pyramidal complex with a 1,4,8,11-tetramethyl-1,4,8,11-tetraazadodecane ligand in which the exogenous hydroxido ligand is derived from dioxygen [22], and Levy has prepared a trigonal bipyramidal complex with a bulky Schiff base ligand where the exogenous hydroxido ligand is derived from adventitious water [23]. The earliest structurally characterized 5-coordinate terminal Ni II –OH 2 complex was reported by Stuky in 1969 [24], and since then many other structurally characterized terminal Ni II –OH 2 complexes have been prepared [2527].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative comparison between 2 and the isostructural trans -1,2-peroxo bridged dinickel complex, {[Ni(tmc)] 2 ( μ -O 2 )} 2+ ( 4 ),13 is instructive. Because the disulfide π * orbitals in 2 are higher in energy than the peroxo π * orbitals in 4 , the former are closer in energy to the nickel 3d orbitals and, thus, interact more strongly to produce more covalent Ni–S bonds in 2 compared to the Ni–O bonds in 4 .…”
mentioning
confidence: 99%
“…1-3 Ni͑tmc͒ + ͑tmc= 1,4,8,11-tetramethyl-1, 4,8,11-tetrazadodecane͒ has been investigated for their potential use in forming various Ni-O intermediates in many applications. 4 Ni compounds such as Ni 2 S 3 have been known to be carcinogenic. 5,6 Although a molecular level understanding of carcinogenesis of Ni is lacking, one of the mechanisms suggested that a square-planar binding of Ni ͑II͒ to a peptide motif in the C-tail region of histone H2A helped the hydrolysis of peptides.…”
Section: Introductionmentioning
confidence: 99%